Tinjauan Penambahan Mineral Zn dalam Pakan Terhadap Kualitas Spermatozoa pada Sapi Frisian holstein Jantan - Sus Derthi Widhyari; Anita Esfandiari; Agus Wijaya; Retno Wulansari; Setyo Widodo; Leni Maylina (Institut Pertanian Bogor, 2015)
Bulls are expected to be able to produce a good quality and quantity of sperm. The objective of this experiment was to study the effect of Zn supplementation on the sperm quality, in Frisian holstein bulls. Ten bulls, 1618 months of age were used in this experiment. The experimental bulls were divided into two groups, i.e.,group without Zn supplementation (control) and group with 60 ppm of Zn supplementation. Zn supplementations were given everyday for a period of four months. Semen was collected by using artificial vaginaat the end of the experiment. Semen quality was evaluated macroscopically and microscopically. The variables measured were semen volume, semen pH, sperm motility, sperm concentration, sperm viability, and sperm abnormality. The results showed that Zn supplementation significantly increased sperm motility and sperm concentration (P<0.05), whereas there was no significant difference in other parameters.